The economic impacts of temperature on industrial productivity: Evidence from Indian manufacturing - Anant Sudarshan; Meenu Tewari (Indian Council for Research on International Economic Relations (ICRIER), 2014)
We provide empirical evidence indicating that changes in surface temperatures may directly impact manufacturing output through their impact on worker productivity. We utilize a multi-year panel of manufacturing plants in India, as well as daily worker productivity measures from selected case-study units to show that (i) manufacturing output decreases at high temperatures by 1-3 percent per degree celsius; (ii) this reduction appears to be driven by declining worker productivity. Our results suggest that climate-economy models may underestimate the costs of climate change by neglecting to account for reduced worker productivity. The causal channel we identify could explain a portion of the strong negative correlation observed between temperature and GDP.
Keywords: Q54; Q56; 330; temperature; worker productivity; industry; climate change